Uncovering Trait Associations Resulting in Maximal Seed Yield in Winter and Spring Oilseed Rape - Siles, Laura; Hassall, Kirsty L.; Sanchis Gritsch, Cristina; Eastmond, Peter J.; Kurup, Smita (Frontiers in Plant Science, 2021)
Seed yield is a complex trait for many crop species including oilseed rape (Brassica napus), the second most important oilseed crop worldwide. Studies have focused on the contribution of distinct factors in seed yield such as environmental cues, agronomical practices, growth conditions or specific phenotypic traits at the whole plant level, such as number of pods in a plant. However, how female reproductive traits contribute to whole plant level traits, and hence to seed yield, has been largely ignored. Here, we describe the combined contribution of 33 phenotypic traits within a B. napus diversity set population and their trade-offs at the whole plant and organ level, along with their interaction with plant level traits. Our results revealed that both winter and spring oilseed rape; the two more economically important oilseed rape groups in terms of oil production; share a common dominant reproductive strategy for seed yield. In this strategy the main inflorescence is the principal source of seed yield, producing a good number of ovules, a large number of long pods with a concomitantly high number of seeds per pod. Moreover, we observed that winter oilseed rape opted for additional reproductive strategies than spring oilseed rape, presenting more plasticity to maximise seed yield. Overall, we conclude that oilseed rape adopts a key strategy to ensure maximal seed yield and propose an ideal ideotype highlighting crucial phenotypic traits that could be potential targets for breeding.